COVID-19 Mortality Underreporting in Brazil: Analysis of Data From Government Internet Portals - Veiga e Silva, Lena; de Andrade Abi Harb, Maria Da Penha; Teixeira Barbosa dos Santos, Aurea Milene; de Mattos Teixeira, Carlos André; Macedo Gomes, Vitor Hugo; Silva Cardoso, Evelin Helena; S da Silva, Marcelino; Vijaykumar, N L; Venâncio Carvalho, Solon; Ponce de Leon Ferreira de Carvalho, André; Lisboa Frances, Carlos Renato (JMIR Publications, 2020)
BackgroundIn Brazil, a substantial number of coronavirus disease (COVID-19) cases and deaths have been reported. It has become the second most affected country worldwide, as of June 9, 2020. Official Brazilian government sources present contradictory data on the impact of the disease; thus, it is possible that the actual number of infected individuals and deaths in Brazil is far larger than those officially reported. It is very likely that the actual spread of the disease has been underestimated. ObjectiveThis study investigates the underreporting of cases and deaths related to COVID-19 in the most affected cities in Brazil, based on public data available from official Brazilian government internet portals, to identify the actual impact of the pandemic. MethodsWe used data from historical deaths due to respiratory problems and other natural causes from two public portals: DATASUS (Department of Informatics of the Unified Healthcare System) (2010-2018) and the Brazilian Transparency Portal of Civil Registry (2019-2020). These data were used to build time-series models (modular regressions) to predict the expected mortality patterns for 2020. The forecasts were used to estimate the possible number of deaths that were incorrectly registered during the pandemic and posted on government internet portals in the most affected cities in the country. ResultsOur model found a significant difference between the real and expected values. The number of deaths due to severe acute respiratory syndrome (SARS) was considerably higher in all cities, with increases between 493% and 5820%. This sudden increase may be associated with errors in reporting. An average underreporting of 40.68% (range 25.9%-62.7%) is estimated for COVID-19-related deaths. ConclusionsThe significant rates of underreporting of deaths analyzed in our study demonstrate that officially released numbers are much lower than actual numbers, making it impossible for the authorities to implement a more effective pandemic response. Based on analyses carried out using different fatality rates, it can be inferred that Brazil's epidemic is worsening, and the actual number of infectees could already be between 1 to 5.4 million.